Orientation-dependent stress evolution in diamond abrasive grains under directional loading - Brune, Gabriel; Tsagkir Dereli, Tountzer; Olschewski, Lars; Lopes Dias, Nelson Filipe; Kipp, Monika; Biermann, Dirk; Debus, Jörg (Technische Universität Dortmund, 2026)
Understanding the response of diamond abrasive grains to mechanical loading remains crucial for optimizing their performance in precision manufacturing. In that context, the role of the initial residual stress and crystallographic orientation of the grains is poorly understood. We investigate synthetic diamond grains in two different grit sizes (D126, D252) subjected to directional loading up to 100 N using x-ray diffraction and spatially resolved Raman spectroscopy. Small grains with preferential (111) orientation show an unexpected stress evolution under contact pressures up to 16 GPa, with Raman shifts increasing from 1331.3 to 1333.0cm−1, indicating an enhanced local compressive stress state at the probed surface regions. Conversely, large (311)-oriented grains exhibit a heterogeneous stress development with Raman shifts varying from 1331.5 to 1332.6cm−1, including regions that become more tensile (or less compressive) relative to their initial state. The relationship between the relative Raman shift and a spatially weighted contact pressure follows an empirical power law 𝛿⁢𝐸∝𝑝′𝛼c with opposite, orientation-dependent exponents: 𝛼≈+0.25 for (111) grains showing progressive compression enhancement and 𝛼≈−0.35 for (311) grains exhibiting a trend toward tensile stress components with increasing load. Molecular dynamics simulations reveal that the Schmid factor governs this orientation-dependent response: The low Schmid factor (0.27) for [111] loading restricts dislocation glide, leading to stress retention with high elastic recovery, while the high Schmid factor (0.45) for [311] loading facilitates plastic flow and stress relaxation despite lower peak stress. These findings demonstrate that stress evolution in diamond under directional loading is controlled by the geometric relationship between loading direction and slip systems, providing mechanistic insights for diamond tool design.
Physical review research; 8(2)
Keywords: Abrasion; Grain boundaries; Strain; Stress; Tribology; Diamond; Density functional theory; Optical microscopy; Raman spectroscopy; X-ray diffraction; 530